2014
DOI: 10.1371/journal.ppat.1004351
|View full text |Cite
|
Sign up to set email alerts
|

The Cofilin Phosphatase Slingshot Homolog 1 (SSH1) Links NOD1 Signaling to Actin Remodeling

Abstract: NOD1 is an intracellular pathogen recognition receptor that contributes to anti-bacterial innate immune responses, adaptive immunity and tissue homeostasis. NOD1-induced signaling relies on actin remodeling, however, the details of the connection of NOD1 and the actin cytoskeleton remained elusive. Here, we identified in a druggable-genome wide siRNA screen the cofilin phosphatase SSH1 as a specific and essential component of the NOD1 pathway. We show that depletion of SSH1 impaired pathogen induced NOD1 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 41 publications
5
47
0
Order By: Relevance
“…Supporting our results, RIPK2 was identified in immunoprecipitations with 14-3-3 previously (Pozuelo Rubio, Geraghty et al, 2004) and 14-3-3 proteins might regulate RIPK2 signaling as at least 14-3-3- appeared as a candidate of a negative regulator of NOD1 and NOD2 signaling in two independent siRNA screens (Bielig, Lautz et al, 2014, Warner, Burberry et al, 2013, Warner, Burberry et al, 2014. Moreover, 14-3-3 binds RIPK3 (Zhang, Shao et al, 2009) and regulates its activity by regulating TSC2 binding (Fettweis, Di Valentin et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…Supporting our results, RIPK2 was identified in immunoprecipitations with 14-3-3 previously (Pozuelo Rubio, Geraghty et al, 2004) and 14-3-3 proteins might regulate RIPK2 signaling as at least 14-3-3- appeared as a candidate of a negative regulator of NOD1 and NOD2 signaling in two independent siRNA screens (Bielig, Lautz et al, 2014, Warner, Burberry et al, 2013, Warner, Burberry et al, 2014. Moreover, 14-3-3 binds RIPK3 (Zhang, Shao et al, 2009) and regulates its activity by regulating TSC2 binding (Fettweis, Di Valentin et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…NOD1 and NOD2, could be found at the plasma membrane in association with F actin, which is needed for downstream activation of NF-B signaling (42,51). Recently, Bielig et al have shown that the actin depolymerization factor (ADF)/cofilin phosphatase SSH1 is an essential component of the NOD1 pathway, which plays a role in activation of NF-B and cell responses to Shigella infection (52). Indeed, depletion of SSH1 mRNA resulted in reduced production of IL-8 and IL-6 following infection of HeLa cells with Shigella flexneri strain M90T.…”
Section: Discussionmentioning
confidence: 99%
“…These features are of particular importance in the gastrointestinal system, where chronic inflammation and tissue damage act as tumor promoters (Quante and Wang, 2008), but our understanding of the underlying regulatory network is still incomplete for many inducers. Several RNAi loss-of-function studies have identified factors involved in NF-kB pathway activation, including stimuli of the nucleotide-binding oligomerization domain-containing protein (NOD)1 and NOD2 receptors (Bielig et al, 2014;Lipinski et al, 2012;Warner et al, 2013;Yeretssian et al, 2011), Epstein-Barr virus (Gewurz et al, 2012), Neisseria gonorrhoeae (Gaudet et al, 2015), and Shigella flexneri infections (Milivojevic et al, 2017). These studies have shown that NF-kB signaling, although sharing core elements, is highly complex and diverse.…”
Section: Introductionmentioning
confidence: 99%